Environmental degradation of fracture resistance in high-temperature water environments of low-alloy reactor pressure vessel steels with high sulphur or phosphorus contents. (1st July 2019) - Que, Z.; Seifert, H.P.; Spätig, P.; Holzer, J.; Zhang, A.; Rao, G.S.; Ritter, S.
Highlights: Elastic plastic fracture mechanics tests on RPV steels with high environmentally-assisted cracking or temper embrittlement susceptibilities revealed a clear, but moderate reduction of the fracture initiation resistance in high-temperature water. In RPV steel with high phosphorus content and high temper embrittlement susceptibility, the reduction of fracture initiation resistance was most pronounced in hydrogenated high-temperature water. The interaction of weakened grain boundaries and localized plastic deformation resulted in cracking at lower stresses/strains and the early formation and growth of micro-voids. In RPV steel with high sulphur content and high environmentally-assisted cracking susceptibility, the strongest environmental reduction occurred in oxygenated high-temperature water with aggressive occluded crevice environment. The aggressive occluded crack crevice chemistry increases the hydrogen availability and uptake, which results in higher level of localization of plastic deformation at the crack tip. Abstract: The fracture behaviour of low-alloy reactor pressure vessel steels with various sulphur and phosphorus contents, different environmentally-assisted cracking (EAC) and temper embrittlement (TE) susceptibilities was evaluated by elastic plastic fracture mechanics tests in air and various simulated light water reactors environments. A moderate but clear reduction of fracture initiation resistance occurred in a) high-sulphur steel with high EAC susceptibility in oxygenated high-temperature water with aggressive occluded crevice environment and preceding EAC growth, and in b) high-phosphorus steel with high TE susceptibility, where the reduction of fracture resistance was most pronounced in hydrogenated high-temperature water.